Rehabilitation, the Concession of New Life to Old Buildings - Farhad Fakhar Tehrani; Ahmad Asgarian jedi; Bahram Ghadiri (صفه)
Rehabilitation and reconstruction, its more commonly known branch, have been highly regarded in the previous decades throughout the world. With regardes to the consideration of this field by executives, cultural directors and even the public in the previous years, the present article aims at the introduction and designation of the boundaries of rehabilitation.